The effect of different sweeteners on the free radical scavenging activities, alcohol contents, sugar reductions, and hedonic properties of green tea kombucha - Muhammad Shidiq Rukman; Ayu Nala El Muna Haerussana; Ayu Nala El Muna Haerussana (Faculty of Pharmacy, Mahidol University, 2023)
Green tea (Camellia sinensis) consumption has increased due to the compounds in green tea that have health benefits. Fermenting brewed green tea with a Symbiotic Culture of Bacteria and Yeast (SCOBY) to create green tea kombucha is a suitable strategy to raise that benefit. Free-radical scavenging activity, alcohol level, sugar reduction, and the hedonic test (color, aroma, and flavor hedonic test) were used to determine the quality of kombucha. This study determined how various sweeteners influence that parameter using DPPH (2,2-diphenyl-1-picrylhydrazyl) method to determine free-radical scavenging activity; distillation, and specific weight to determine alcohol level; refractometer to determine sugar reduction content; and scoring preference from 30 panelists to determined hedonic. This study revealed that the IC50 value of kombucha ranged between 33.44 and 38.85 ppm. The honey yielded the highest alcohol content, 2.78%, while stevia yielded the lowest, 2.36%. The range of reducing sugar content is 18.99 to 88.90 grams. The color, aroma, and flavor of green tea kombucha are enhanced by adding stevia, honey, palm sugar, and refined sugar, respectively. Our findings showed that green tea kombucha had very strong radical scavenging activity in various sweeteners. Stevia had the highest radical scavenging activity and was deemed the best by the panel. Stevia also showed the lowest levels of alcohol and sugar reduction. However, additional other sweeteners must be investigated to determine the health benefits of kombucha.